Economic Value and Carbon Emission Reduction Scenarios from Kon Ha Nung Forest Change, Gia Lai Province 2022-2030 - Hieu, Nguyen Huu Viet; Ngoc Thach, Nguyen; Van Manh, Pham; Anh Tung, Nguyen; Anh Hung, Le (VNU Journal of Science: Earth and Environmental Sciences; Vol 41 No 1DO - 10.25073/2588-1094/vnuees.5177, 2025)
This study presents a method for above-ground biomass estimation and a machine learning method to assess changes in forest status for the period 2000 - 2022. From there, the economic value obtained from conserving and developing natural forests will be determined according to scenarios for reducing deforestation and forest degradation up to 2030. The study area was selected in Kon Ha Nung plateau, Gia Lai province, where the forest area is large, the ecosystem is relatively intact, and has high biodiversity. The study uses standard plots measured in 2000, 2010, and 2022 and a linear regression equation to estimate biomass from SPOT-4 images in the form of Lin-Log with R 2 = 0,72 and the root-mean-square error RMSE reached 22,87 Mg/ha while the equation applied to Sentinel-2 images in 2022 was Log-Lin with R 2 = 0,759 and RMSE reached 19,50 Mg/ha. The research results showed that the forest status of the study area from 2000 to 2022 had large fluctuations within 20 years from 2000 to 2022: The total area of ​​deforestation reached 56.159,9 ha, the area of ​​forest degradation was 17.206,4 ha; of which the area of ​​natural forest increased by 5.603,3 ha, the area of ​​forest quality improvement reached 19.207,3 ha. The total area of ​​deforestation and forest degradation in the Kon Ha Nung plateau was larger than the total area of ​​natural forest increased and forest quality improved. The study estimates the economic value gained from participating in the carbon market with three CO 2 emission reduction scenarios for the period 2022 - 2030 through forest change analysis for the two periods 2000 - 2010 and 2010 - 2022. The research results provide an overview of income sources from ecosystem services in the Kon Ha Nung plateau from forest protection and development activities. Keywords : CO 2 emissions, deforestation, forest degradation, REDD+, biomass.